"Math Gives Me a Tummy Ache!" Mathematics Anxiety in Kindergarten. Issue 2 (3rd April 2021) - Lu, Yaheng; Li, Qian; Patrick, Helen; Mantzicopoulos, Panayota
Abstract: We report on the construction and validation of the Young Children's Math Anxiety Scale (YCMAX), a developmentally appropriate measure of math anxiety intended for kindergarten students. We administered the YCMAX to a sample of public school kindergarteners ( N  = 355) and conducted factor analyses to examine its structure. A two-factor solution (Worry and Somatization) best fit the data. Children with higher, compared to lower, Worry and Somatization scores had lower math achievement, reported feeling less competent at math, liked math less, and were evaluated by their teachers as less interested in and needing more support for learning math. In addition, we documented children's experiences with math tests using three open-ended questions. More than half of the children ( n  = 216, 61%) commented on their math tests, including test procedures, test content, and test results. Children who felt negatively about math tests expressed more worry and, particularly, more somatization compared to those with positive feelings about math tests. The results indicated that the YCMAX scores were internally consistent and demonstrated construct validity, thus supporting the instrument's utility for research on math anxiety in the early grades.